The market approach to local markets of housing and communal services of Ukraine - Lisyuk, V.; Serov, A. (Економічний вісник Донбасу, 2016)
The article is devoted to research of the problems of housing and communal services of Ukraine. The paper identified the most significant problems of utilities, the generalized cost of maintaining the housing stock are given, the problematic points of the tariff for the maintenance of houses and local area are disclosed. The possible ways of solving the problem moments of industry. The need to reform the sector and the ineffectiveness of the reforms taking place in our time are caused. Стаття присвячена дослідженню існуючих проблем житлово-комунального господарства України. Визначено найбільш суттєві проблеми ЖКГ, надано узагальнені витрати на утримання житлового фонду, розкрито проблемні пункти, із яких складається тариф на СДПТ. Запропоновано можливі шляхи вирішення проблемних моментів галузі. Обумовлена необхідність термінового реформування галузі і неефективність реформ, які проводяться в наш час. Статья посвящена исследованию существующих проблем жилищно-коммунального хозяйства Украины. Определены наиболее существенные проблемы ЖКХ, даны обобщённые расходы на содержание жилого фонда, раскрыты проблемные пункты, из которых состоит тариф на СДПТ. Предложены возможные пути решения проблемных моментов отрасли. Обусловлена необходимость срочного реформирования отрасли и неэффективность реформ, которые проводятся в наше время.